Mobile magic : the Saatchi & Saatchi guide to mobile marketing - Eslinger, Tom (Wiley, 2014)
"A real-world guide to mobile marketing from the head of digital initiatives at Saatchi & Saatchi worldwide. The future of marketing is mobile, with seventy-five percent of the world's population having access to a mobile phone and the average American spending 82 minutes per day using her phone for activities other than talking. To traditional marketers unfamiliar with the special challenges of mobile marketing, this territory feels complicated and even frightening. Mobile magic provides a bird's-eye view of the process of creating great mobile marketing from one of the world's most experienced and successful practitioners"--